The development of mobile application for parking lot management at university campus - Ng, Kah Weng (2020)
This project is a campus parking mobile application project for academic purpose. The aim of this project is to develop a parking system that replace current old fashion system that can improve effectiveness during looking for parking space, to show the availability of parking space, and to remind user their vehicle location. The current parking system in the campus is not effective enough. Therefore, by implementing this project will improve the effectiveness and reduce the time needed to find a parking slot. Due to different obstacle faced, Quick Response (QR) are the best suited method to implement into the system. This system will improve student time management, reduce empty parking space time wasting. Other than that, the data of student can be gather from this system which can be further implement or perform behavior analysis on the user.